Leadership, education, personality an interdisciplinary journal.
This interdisciplinary and transfer oriented journal deals with the topics of Leadership, Personality and Education as well as the areas of conflict arising from this combination.. The journal aims for a comprehensive and diverse approach to the research fields concerned, so that articles from all scientific disciplines are welcomed.